Monolithically Integrated Circuits from Functional Oxides. Issue 1 (24th November 2013) - Jany, Rainer; Richter, Christoph; Woltmann, Carsten; Pfanzelt, Georg; Förg, Benjamin; Rommel, Marcus; Reindl, Thomas; Waizmann, Ulrike; Weis, Jürgen; Mundy, Julia A.; Muller, David A.; Boschker, Hans; et al.
<x xml:space="preserve">Abstract</x> The rich array of conventional and exotic electronic properties that can be generated by oxide heterostructures is of great potential value for device applications. However, only single transistors bare of any circuit functionality have been realized from complex oxides. Here, monolithically‐integrated n‐type metal‐oxide‐semiconductor logic circuits are reported that utilize the two‐dimensional electron liquid generated at the LaAlO3/SrTiO3 interface. Providing the capability to process the signals of functional oxide devices such as sensors directly on oxide chips, these results illustrate the practicability and the potential of oxide electronics.